Efficient genomic DNA extraction protocol from medicinal rich Passiflora foetida containing high level of polysaccharide and polyphenol - Lade, Bipin Deochand (Springer International Publishing, 2014)
In Present work, the main objective is to develop less time consuming protocol for genomic DNA isolation from leaves of Passiflora foetida. Optimized protocol is cost effective, as it avoided use of expensive liquid nitrogen. The important parameters of CTAB buffer composition such as Polyvinylpyrrolidone PVP40000 (without PVP, 1%, 2%, 3.5%, 4.0%, 4.5%, 5.0%), CTAB (w, 1%, 2%, 3%, 4%, 5%), water bath temperature (30°C to 70°C) and duration on water bath for half hr and one and half hr has been optimized. CTAB (2%), PVP (1%), water bath temperature (70%), duration on water bath (1 hr) has efficiently yielded DNA quality of 200-1782 μg/0.5gm from leaf, stem, root, tendril and flower. However, 168 μg - 1782 μg of DNA has been obtained from 0.5 g of leaf of Passiflora foetida. Polyphenol contamination has been overcome using 5M NaCl and PVP. Acetate has been used for obtaining double-stranded DNA in stabilized form. Current DNA extraction protocol takes maximum of four hours for completion, which is many time savings. RAPD-PCR reaction parameters such as DNA concentration (100ng), Primer concentration (2 μM), Dream Taq polymerase (2 U), annealing temperature (29°C) and number of cycles for amplification of DNA has been optimized. Primer fragment Akansha 7 shows high polymorphism of 7 fragments ranges from 200bp – 2500 bp. Current optimized protocol of DNA isolation is specifically for Passiflora foetida, which can be used for downstream molecular techniques.